2009
DOI: 10.2172/1028891
|View full text |Cite
|
Sign up to set email alerts
|

Handbook on dynamics of jointed structures.

Abstract: The problem of understanding and modeling the complicated physics underlying the action and response of the interfaces in typical structures under dynamic loading conditions has occupied researchers for many decades. This handbook presents an integrated approach to the goal of dynamic modeling of typical jointed structures, beginning with a mathematical assessment of experimental or simulation data, development of constitutive models to account for load histories to deformation, establishment of kinematic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 50 publications
5
26
0
Order By: Relevance
“…DP4 is omitted since it did not produce a high enough Mode 1 amplitude. The damping for Mode 1 decreases with increasing amplitude, which is the opposite of what one would expect for a microslip joint nonlinearity [9], suggesting the nonlinearity in this mode is dominated by something other than microslip.…”
Section: Resultsmentioning
confidence: 57%
“…DP4 is omitted since it did not produce a high enough Mode 1 amplitude. The damping for Mode 1 decreases with increasing amplitude, which is the opposite of what one would expect for a microslip joint nonlinearity [9], suggesting the nonlinearity in this mode is dominated by something other than microslip.…”
Section: Resultsmentioning
confidence: 57%
“…Complex structures in engineering practice are commonly assembled by a large number of jointing components. Recent investigations (Ames et al, 2009; Gaul and Schmidt, 2019; Xiao et al, 2014) have shown that micro- and macro-slipping will occur on contact interfaces of jointing components under external loads. These phenomena are responsible for nonlinear contact stiffness and structural damping (Bograd et al, 2011; Gaul and Nitsche, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of Iwan model depends on precise experimental data of jointed structures. Quasi-static experimental investigations (Ames et al, 2009; Eriten et al, 2012; Resor and Starr, 2008; Xu et al, 2020) indicate a weak nonlinearity of contact stiffness during micro-slip stage, which is relatively difficult to capture. Therefore, measuring joint damping through dynamic experiments is often considered.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the dynamical response for nonlinear joint models, this would require iterative solvers. Most existing mod-elling approaches including the non-linear contact friction models employ either time domain solvers [7] (e.g.Runge-Kutta or Newmark method [8]) or frequency domain solvers [6,9] (e.g.harmonic balance methods (HBM)). To solve the full scale jointed model without reduction for a wide range of frequencies or time, the computational expense with these solvers is usually unacceptable.…”
Section: Introductionmentioning
confidence: 99%